PHYSICS LEARNING MEDIA TO BUILD HIGH SCHOOL STUDENT'S UNDERSTANDING OF MOMENTUM MATERIAL - Rahayu, Anisa Tri; Jannah, Nurul; Lestari, Dwi Ayu; Gumilar, Teguh (UIN Sunan Gunung Djati Bandung, 2022)
For most students, physics is one of the boring subjects and is considered difficult, the subject that is considered difficult is momentum, the level of students' understanding of the momentum material is still low. The use of learning media aims to facilitate the delivery of learning so that students can easily and efficiently achieve learning objectives. Therefore, the researcher considers the need for supporting learning media as an alternative to physics learning media on the concept of momentum, as well as testing the feasibility of media to support learning. The method used by researchers in research and development (R&D) following the steps of Borg and Gall, steps are developing products and testing the effectiveness of products to achieve goals. Meanwhile, data collection was carried out by distributing instruments in the form of questionnaires and LKPD to measure learning achievement and student responses. Based on the results of the study, all questionnaire scores scored almost four in the good category, and all students were able to answer the LKPD. Therefore, with the media students can construct an understanding of the concept of momentum. Students who previously did not know the concept of momentum became aware of it even to the point of being able to formulate its meaning mathematically. With the existence of learning media, learning physics on the concept of momentum becomes more fun, interesting, and can increase students' learning motivation.